Effect of seasons and fishing ban period on umami-related and functional components of greeneye (Chlorophthalmus albatrossis) from Japanese coast - Horie, Ryohei; Imagawa, Takumi; Uchida, Katsuhisa; Taoka, Yousuke; Tanaka, Ryusuke (Journal of food composition and analysis, 2025)
Greeneye (Chlorophthalmus albatrossis) is a small fish with a mild white flesh and texture that can be eaten with bones. In this study, we aimed to clarify the effect of season and fishing ban period of greeneyes in terms of umami-related and functional component values by analyzing their chemical components. Greeneyes from the Japanese coast were analyzed between March 2023 (spring) and February 2024 (winter), excluding the fishing ban period on June 2023. Free amino acids and nucleic acid-related substances were analyzed as components associated with umami-related components. The free amino acid level was the highest (3619.13 ± 719.54 µg/g wet sample) in the spring before the fishing ban, while the inosine monophosphate level in autumn was the highest (3884.28 ± 666.56 µg/g wet sample). Therefore, the umami taste was higher in spring and autumn. The levels of functional components (lipid content, fatty acids, vitamin E, and imidazole dipeptides) increased following the implementation of the fishing ban. Calcium levels were approximately 5 mg/g sample, with no significant differences observed in all seasons; the level was comparable to other fish consumed with bones or alternative high-calcium food sources. In conclusion, greeneyes can be considered a stable source of calcium and fish throughout the year, with varying umami-related and functional components depending on the season. [Display omitted] •Free amino acid levels were highest in the spring before the fishing ban.•Inosine monophosphate level was the highest in autumn after the fishing ban.•Lipid content was highest in summer after the fishing ban.•Calcium levels showed no significant changes throughout the year.•Calcium levels were comparable to other calcium-rich food sources.